On a Flow-Shop Scheduling Problem with Fuzzy Pentagonal Processing Time. (28th April 2021) - Alharbi, Majed G.; El-Wahed Khalifa, Hamiden Abd
Abstract : Scheduling involves planning and arranging jobs across a coordinated set of events to satisfy the customer's demands. In this article, we present a simple approach for the flow-shop (FS) scheduling problem under fuzzy environment in which processing time of jobs are represented by pentagonal fuzzy numbers. This study is intended to reduce the rental cost of the machine in compliance with the rental policy. The fuzzy FS scheduling problem is solved without converting the processing time into its equivalent crisp numbers using a robust ranking technique and a fuzzy arithmetic pentagonal fuzzy numbers. A numerical illustration indicates that the approach is workable, accurate, and relevant.